El análisis del discurso en la investigación social - Lara Romero, Gladys (Enunciación, 2004)
This article suggests a general dynamics of the textual study focused in the enunciation, and itestablishes relations with categories of the Sociology of Language (context of situation, registration, code), the sociology(habitus, field) and of the semiotics of culture (semeiosphere, culture, text, code), with the purpose of describing, explaining and interpreting the discourses, by conceiving them as objectivations or objectivities The theoretical and methodological pattern that is formulated in this proposal contributes to the pursuit of an articulation between the disciplines that are in charge of the observation, the reflection and the comprehensive interpretation of the social actions.